2005
DOI: 10.1093/molbev/msi248
|View full text |Cite
|
Sign up to set email alerts
|

Mitochondrial DNA from Prehistoric Canids Highlights Relationships Between Dogs and South-East European Wolves

Abstract: The question of the origins of the dog has been much debated. The dog is descended from the wolf that at the end of the last glaciation (the archaeologically hypothesized period of dog domestication) was one of the most widespread among Holarctic mammals. Scenarios provided by genetic studies range from multiple dog-founding events to a single origin in East Asia. The earliest fossil dogs, dated approximately 17-12,000 radiocarbon ((14)C) years ago (YA), were found in Europe and in the Middle East. Ancient DNA… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

6
81
1

Year Published

2007
2007
2014
2014

Publication Types

Select...
7
3

Relationship

0
10

Authors

Journals

citations
Cited by 68 publications
(88 citation statements)
references
References 37 publications
6
81
1
Order By: Relevance
“…The sequence divergence between the Tibetan Mastiff and the gray wolf (0.70) was smaller than that between the Tibetan Mastiff and the Tibetan wolf (3.30), and between the Tibetan Mastiff and coyote (5.27). This suggested that the Tibetan Mastiff originated from the gray wolf, the same as with other domestic dogs (Vilà et al, 1997;Leonard et al, 2002;Verginelli et al, 2005;Boyko et al, 2009;Pang et al, 2009), and is consistent with the results of Li et al (2008). For the protein-coding genes, tRNAs and rRNAs, a decreasing trend in the number of identified variable sites, also showed that there was a closer relationship between domestic dogs and gray wolves than between domestic dogs and coyotes.…”
Section: Discussionsupporting
confidence: 81%
“…The sequence divergence between the Tibetan Mastiff and the gray wolf (0.70) was smaller than that between the Tibetan Mastiff and the Tibetan wolf (3.30), and between the Tibetan Mastiff and coyote (5.27). This suggested that the Tibetan Mastiff originated from the gray wolf, the same as with other domestic dogs (Vilà et al, 1997;Leonard et al, 2002;Verginelli et al, 2005;Boyko et al, 2009;Pang et al, 2009), and is consistent with the results of Li et al (2008). For the protein-coding genes, tRNAs and rRNAs, a decreasing trend in the number of identified variable sites, also showed that there was a closer relationship between domestic dogs and gray wolves than between domestic dogs and coyotes.…”
Section: Discussionsupporting
confidence: 81%
“…4a). However, none of the feral dogs sampled exhibited pure dog ancestry, although this may reflect recent common ancestry between the two species (see Verginelli et al 2005). Ten individuals with a grey wolf phenotype showed signs of admixture with dogs.…”
Section: Kinship and Spatial Distribution Of Kinmentioning
confidence: 99%
“…However, modern DNA can be skewed by thousands of years of artificial selection. With the development of new archaeological techniques, ancient DNA recovered from animal remains can provide a direct window into the process of animal domestication and breeding, which has been previously successfully used in the study of cattle (Troy et al, 2001;Bollongino et al, 2006;Beja-Pereira et al, 2006;Edwards et al, 2007), dogs (Leonard et al, 2002;Verginelli et al, 2005), goats (Fernández et al, 2002), horses (Vilà et al, 2001;Cai et al, 2009), and pigs (Watanobe et al, 2002;Larson et al, 2007a,b). In contrast to other domestic animals, only a few ancient DNA studies have focused on the origin and domestication of sheep (Bar-Gal et al, 2003;Cai et al, 2007).…”
Section: Introductionmentioning
confidence: 99%